The impact of felling method, bunch size, slope degree and skidding area on productivity and costs of skidding in a eucalyptus plantation - Miyajima, Ricardo Hideaki [UNESP]; Fenner, Paulo Torres [UNESP]; Batistela, Gislaine Cristina [UNESP]; Simões, Danilo [UNESP] (University of Zagreb, Faculty of Forestry and Wood Technology, 2021)
Grapple skidder is a machine designed for the extraction of tree bunches after felling. Several factors influence its technical performance and costs such as terrain slope, operator experience time, machine type, and the size of tree bunches for each operating cycle, among others. Thus, it becomes necessary to weigh the variables that most influence the productivity and costs of the grapple skidder. So, the main objective was evaluated according to the influence of bunch size using two feller bunchers with distinct technical characteristics, two slope classes and two skidding areas on the productivity and machine production cost in a Eucalyptus plantation. For the analysis of the productivity, the study of time and method was applied and the scheduled machine cost per hour was based on the Food and Agriculture Organization of the United Nations methods. When analyzing the results, it was found that the operational ele-ments moving without load (MWoL) and moving with load (MWL) were the ones that spend the most time in the operational cycle of the grapple skidder. Among the cost components, monetary expenditure on fuel and operator labor were the most influential in the scheduled machine cost per hour. In conclusion, the tree bunches and slope class influenced the productivity and, consequently, the cost of the skidding operation.
Keywords: Forestry; Optimization; Production cost; Time and motion; Wood harvesting